Preparation of poly methyl methacrylate thin film by solution casting method to study its ultrasonic velocity - Kale, M. A.; A. Kale, Rashmi (International Journal of Physical Research, 2018)
Polymers are long chain giant organic molecules are assembled from many smaller molecules called monomers. The work reflects the preparation of poly methyl methacrylate thin film by solution casting method. The XRD of PMMA/ZrO2 polymer is taken to confirm the structure and nature of material. Furthermore, it is characterized by finding the ultrasonic velocity at different concentration of ZrO2 and at different temperature keeping the frequency same.